ANALISIS POTENSI BAHAYA UNTUK MEMINIMALISIR RISIKO KECELAKAAN KERJA PADA PROYEK PEMBANGUNAN JETTY PLTMGU LOMBOK PEAKER DI PT. XYZ MENGGUNAKAN METODE HIRARC (HAZARD IDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL) - Riskawati; Iksan Adiasa; Didi Rahman (Jurnal Industri dan Teknologi Samawa, 2025)
PT. XYZ is a company engaged in contracting for infrastructure development. In the process of infrastructure development, it is inseparable from the risk of work accidents. Based on the results of observations in the field, the potential for work accidents was found. This study aims to analyze potential hazards and provide improvement proposals to minimize the risk of work accidents in the Lombok Peaker PLTMGU Jetty Construction Project. The method used is HIRARC. HIRARC is used to identify the risk of work accidents as well as analyze hazards and provide improvement proposals to minimize existing risks. The results of the study were identified and there were 8 potential hazards in the construction of the Lombok Peaker PLTMGU jetty construction project, namely 25% potential hazards with low risk levels, 37% potential hazards with high risk levels and 38% potential hazards with extreme risk levels. Improvement proposals that can be given in the Lombok Peaker PLTMGU jetty construction project based on the K3 control hierarchy such as soil erosion around the temporary jetty area, standing under the process of material lifting by cranes and stacking steel pipes by eliminating to eliminate activities in the erosion area. This research is expected to minimize the risk of work accidents in the construction of the Lombok Peaker PLTMGU jetty construction project.